2008
DOI: 10.1002/pnp.92
|View full text |Cite
|
Sign up to set email alerts
|

Cambridge Behavioural Inventory for the diagnosis of dementia

Abstract: The Cambridge Behavioural Inventory (CBI) is a short, self‐administered informant questionnaire developed to distinguish between the behavioural and psychiatric symptoms of Alzheimer's dementia and fronto‐temporal dementia. Here, Dr Hancock and Dr Larner present the results of their study to investigate the diagnostic utility of the Cambridge Behavioural Inventory in a cohort of patients attending their memory clinic. Copyright © 2008 Wiley Interface Ltd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Of these, 85 (59%) were judged to have dementia by DSM-IV criteria and 59 (41%) had no dementia. This dementia prevalence was higher than the approximately 50% recorded in other patient cohorts from these clinics (Hancock and Larner, 2007; 2008b; 2009) but similar to that recorded in a previous study which examined an informant questionnaire (Hancock and Larner, 2008a), presumably reflecting the fact that individuals with no dementia are more likely to attend these clinics without an informant (Larner, 2005).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Of these, 85 (59%) were judged to have dementia by DSM-IV criteria and 59 (41%) had no dementia. This dementia prevalence was higher than the approximately 50% recorded in other patient cohorts from these clinics (Hancock and Larner, 2007; 2008b; 2009) but similar to that recorded in a previous study which examined an informant questionnaire (Hancock and Larner, 2008a), presumably reflecting the fact that individuals with no dementia are more likely to attend these clinics without an informant (Larner, 2005).…”
Section: Resultssupporting
confidence: 86%
“…Compared with another informant questionnaire, the Cambridge Behavioural Inventory (Wedderburn et al ., 2008), which has previously been examined in a demographically similar cohort in these clinics (Hancock and Larner, 2008a), the IQCODE had similar accuracy at the chosen cut-offs, with poorer sensitivity, PPV, DOR, and LR+, but with better specificity, negative predictive value and LR–. Of course, these summary parameters will be dependent on the cut-off chosen: it has been suggested that IQCODE cut-offs should be selected according to the particular application for which the test is being used (Jorm, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall performance of PHQ-9 was similar to that of the CBI, another scale examining behavioural symptoms [17], in terms of test accuracy (0.62 vs. 0.62, respectively) and the sum of sensitivity and specificity (1.30 vs. 1.29, respectively), although the CBI cut-off giving maximal test accuracy had better specificity, positive predictive value, and positive likelihood ratio, but poorer sensitivity, negative predictive value and negative likelihood ratio [14].…”
Section: Discussionsupporting
confidence: 55%
“…PHQ-9 scores were not used in the diagnostic judgment of dementia/no dementia in order to minimize review bias [16]. For those patients who attended with an informant, the latter was invited to complete the Cambridge Behavioural Inventory (CBI) which scores various behavioural and psychiatric symptoms [17], and which has been previously examined in these clinics [14]. The STARD guidelines on reporting diagnostic test accuracy were observed [18].…”
Section: Methodsmentioning
confidence: 99%